A False Positive I-131 Metastatic Survey Caused by Radioactive Iodine Uptake by a Benign Thymic Cyst. (20th December 2017) - Singh, Avneet K.; Bodolan, Adina A.; Gilbert, Matthew P.
Abstract : Thyroid carcinoma is the most common endocrine malignancy in the United States with increasing incidence and diagnosis but stable mortality. Differentiated thyroid cancer rarely presents with distant metastases and is associated with a low risk of morbidity and mortality. Despite this, current protocols recommend remnant ablation with radioactive iodine and evaluation for local and distant metastasis in some patients with higher risk disease. There are several case reports of false positive results of metastatic surveys that are either normal physiologic variants or other pathological findings. Most false positive findings are associated with tissue that has physiologic increased uptake of I-131, such as breast tissue or lung tissue; pathological findings such as thymic cysts are also known to have increased uptake. Our case describes a rare finding of a thymic cyst found on a false positive I-131 metastatic survey. The patient was taken for surgical excision and the final pathology was a benign thymic cyst. Given that pulmonary metastases of differentiated thyroid cancer are rare, thymic cysts, though also rare, must be part of the differential diagnosis for false positive findings on an I-131 survey.